Effects of equivalence ratio and CNG addition on engine performance and emissions in a dual sequential ignition engine. (August 2020) - Yontar, Ahmet Alper; Doğu, Yahya
Compared to widening usage of CNG in commercial gasoline engines, insufficient but increasing number of studies have appeared in the open literature during last decades, while engine characteristics need to be quantified in exact numbers for each specific fuel and engine. CNG usage in spark-ignition engine offers many advantages such as high specific power outputs, knock resistance, and low CO2 emission. Engine performance and emissions are strong functions of equivalence ratio. This study focuses on determination of the effects of equivalence ratio on engine performance and emissions for a unique commercial engine for three fuels of gasoline, CNG, and gasoline–CNG mixture (90%–10%: G9C1). For this aim, the tests and the three-dimensional in-cylinder combustion computational fluid dynamics analyses were employed in quantification of engine characteristics at wide open throttle position. Equivalence ratios were defined between 0.7 and 1.4. The engine's maximum torque speed of 2800 r/min was examined. The tested commercial engine is an intelligent dual sequential ignition engine which has unique features such as diagonally positioned two spark-plugs, dual sequential ignition with variable timing and asymmetrical combustion chamber. This gasoline engine was equipped with an independent CNG port-injection system and a specific engine control unit for CNG. In addition, the engine test system has a concomitant dual fuel delivery system that supplies gas fuel into intake airline while liquid gasoline is injected behind the intake valve. Other than testing the engine, the three-dimensional in-cylinder combustion computational fluid dynamics analyses were performed in Star-CD/es-ice software for the three fuels. The CFD model was built by using renormalization group equations, k–ε turbulence model, and G-equation combustion model. Computational fluid dynamics analyses were run for the compression ratio of 10.8:1, equivalence ratio of 1.1, and engine's maximum torque speed of 2800 r/min. Test results show that brake torque for all fuels increases rapidly from the lean blend to the rich blend. The brake-specific fuel consumption for all fuels decreases from Φ = 0.7 through the stoichiometric region and then slightly increases up to Φ = 1.4. The volumetric efficiencies for three fuels have similar decreasing trend with respect to equivalence ratio. Overall, CNG addition decreases the performance values of torque, brake-specific fuel consumption, volumetric efficiency, brake thermal efficiency, while it decreases emissions of CO2, CO, HC, except NOx . Engine model results show that the maximum in-cylinder pressure is 72 bar at 722 crank angle degree (CAD), 68 bar at 730 CAD, and 60 bar at 735 CAD for gasoline, CNG, and G9C1, respectively. The cumulative heat release for gasoline is 9.09% higher than G9C1, while G9C1 is 15.71% higher than CNG. The CO2 mass fraction for gasoline is about 22.58% lower than G9C1, while it is 40.32% higher than CNG. The maximum mass fraction value of CO is 0.21, 0.17, and 0.08 for gasoline, CNG, and G9C1, respectively. The CO for G9C1 is overall 60.04% lower than CNG and 67.45% lower than gasoline. At maximum point, HC for G9C1 is 31.43% and 71.43% higher than gasoline and CNG, respectively. CNG has the highest level of NOx formation. Maximum NOx mass fractions are 0.0098, 0.0070, and 0.0043 for CNG, G9C1, and gasoline, respectively. After the ignition, the flame development is completed at 1.07, 1.18, and 1.28 ms for gasoline, G9C1, and CNG, respectively. Flame velocities are 28.52, 30.93, and 34.11 m/s for CNG, G9C1, and gasoline, respectively, at 2800 r/min and Φ = 1.1. When the time between ignition moment and top dead center moment is considered, the increment rate of flame center temperature is 904.19, 884.10, and 861.77 K/s for CNG, gasoline, and G9C1, respectively. The highest temperature increment rate occurs for CNG.